Cloning, Expression and Characterization of Hepatitis B Large Surface Antigen In Yeast System - Mohamad Sinang, Fazia (2010)
Hepatitis B virus (HBV) infection is a worldwide health problem, which can lead to severe liver disease mainly hepatocellular carcinoma and cirrhosis. Hepatitis B surface antigen (HBsAg) is a glycoprotein found on the surface of the virus and its presence in the blood is an indicator of positive hepatitis B infection. The existing commercially available vaccine is based on the produced small HBsAg (S-HBsAg) via recombinant DNA technology. Although it is effective, about 5-10% of normal individuals demonstrates no or low response to the standard vaccination schedule. The efficacy of the large HBsAg (L-HBsAg) derived vaccine may differ from S-HBsAg, but such study needs to be conducted to evaluate the potential of L-HBsAg. To date, there is no infonnation on the expression of L-HBsAg intracellularly. Therefore, this study was carried out to express the L-HBsAg protein in yeast Pichia pastoris (P. pastoris) intracellularly. The L-HBsAg gene is inserted into the pPICZ C plasmid and introduced into P. pastoris. The positive clones were confinned by DNA sequencing. Small scale expression of the recombinant L-HBsAg was analyzed by using Western blotting. The glycosylated L-HBsAg of about 42 kDa was detected by Western blotting and its concentration increase from 24 hours to 72 hours sample. The production of L-HBsAg was then scaled up and purified by using sucrose density gradient centrifugation. ELISA showed that the purified L-HBsAg was antigenic. Electron microscopic analysis revealed that the L-HBsAg assembled into spherical particles about 25 nm. The LHBsAg produced in P. pastoris provides an alternative to the vaccines available in market